From centralization to decentralization in Chinese higher education - Xiaohong Qian; Jef C. Verhoeven (Arizona State University, 2004)
Since the late 1970's, the Chinese government has been gradually changing its traditional policy for providing higher education and has begun to emphasize the comprehensiveness of the universities. Interdisciplinary cooperation and the synergization of resources are being promoted, and institutional autonomy is gradually increasing. Schools and faculties have been restored in universities, and new research institutions, research schools, research centers and the like have been established. From a unitary three-level model- university/department/ teaching and research group-before the reform, the organizational structures of the universities have developed a new organizational structure that is more flexible and more open. This more adaptable structure is intended to meet the developmental demands of modern universities with close links being created between their work and regional economic and social development. China has moved from a very centralized educational system in which the main decisions were taken by the central government to a decentralized educational system. This reform is also taking place within the institutions of higher education, and their internal organizational structure has also become more decentralized.